POLA BERAT DAGING RAJUNGAN BERDASARKAN BERAT TUBUH YANG TERTANGKAP DI PERAIRAN SELAT MADURA - Muhammad Zainuri (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2016)
Informations on ratio of meat blue swimming crab weight have both economically and ecological meanings. The aim of this research is to know actual ratio of the weight of meat where as catches on Selat Madura fishing ground. Samples were taken from October 2012 December 2013 and May 2014 November 2014 by longline and trammelnet. The result showed that having tree (3) modes of average ratio of meat blue swimming crab weight which reached highest on May, October and December of year; whereas the percentage of actual the weight of meat ( ratio between average of the weight of meat and body weight) appeared on June and September of year. Consider result of Zainuri (2015) that the 10 cm wide carapace of blue swimming crab identical with 50 g of body weight, the result of this research also be known that there is tendency slightly increased of percentage of actual meat weight on blue swimming crab’s 50 g of body weight and more. Keywords: ratio of meat, Selat Madura, blue swimming crabPATTERN OF CRAB MEAT WEIGHT BASED ON BODY WEIGHT CAUGHT IN THE MADURA STRAITInformation on ratio of meat blue swimming crab weight have both economically and ecological meanings. The aim of this research is to know actual ratio of the weight of meat whereas catches on Madura Strait fishing ground. Samples were taken from October 2012 - December 2013 and May 2014 - November 2014 by long-line and trammel net. The result showed that having tree (3) modes of average ratio of meat blue swimming crab weight which reached highest on May, October and December of year; whereas the percentage of actual the weight of meat (ratio between average of the weight of meat and body weight) appeared on June and September of year. The result of this research also be known that there is tendency slightly increased of percentage of actual meat weight on blue swimming crab’s 50 g of body weight and more. Keywords: Ratio of meat, Body weight, Madura Strait, blue swimming crab